2016
DOI: 10.1103/physreve.94.042309
|View full text |Cite
|
Sign up to set email alerts
|

Network exploration using true self-avoiding walks

Abstract: We study the mean first passage time (MFPT) of true self-avoiding walks (TSAWs) on various networks as a measure of searching efficiency. From the numerical analysis, we find that the MFPT of TSAWs, τ^{TSAW}, approaches the theoretical minimum τ^{th}/N=1/2 on synthetic networks whose degree-degree correlations are positive. On the other hand, for biased random walks (BRWs) we find that the MFPT, τ^{BRW}, depends on the parameter α, which controls the degree-dependent bias. More importantly, we find that the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…The TSAW dynamics; nonetheless, is more analytically tractable than SAW because the former does not depend on a path restart mechanism [13]. Recently, Kim et al [12] showed that the TSAW dynamics is an efficient way to explore complex networks with agents having only the knowledge of the local structure of the network.…”
Section: True Self-avoiding Random Walkmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSAW dynamics; nonetheless, is more analytically tractable than SAW because the former does not depend on a path restart mechanism [13]. Recently, Kim et al [12] showed that the TSAW dynamics is an efficient way to explore complex networks with agents having only the knowledge of the local structure of the network.…”
Section: True Self-avoiding Random Walkmentioning
confidence: 99%
“…The memory aspect is encompassed into the proposed dynamics by an specific type of random walk, the true self-avoiding walk (TSAW), which was found to be one of the most efficient models to explore networks [12]. In the TSAW dynamics, the agent tends to avoid passing through already visited nodes.…”
Section: Introductionmentioning
confidence: 99%
“…random walked biased by the inverse of the degree (RWID) [10], and true self-avoiding walk (TSAW) [3,24]. These walks have been widely employed to study the dynamics of learning curves in the last few years [5,6,28].…”
Section: B Network Dynamicsmentioning
confidence: 99%
“…Network science has been employed to represent a great variety of complex systems [2,7,17,18,20,27]. In recent studies, complex networks have displayed the potential to represent the space of transitions between states for many types of systems [14,24,25]. In this context, the driving processes generating sequences are represented by stochastic walks of a variety of heuristics.…”
Section: Introductionmentioning
confidence: 99%
“…88,90,91 Além deste, recentemente, Kim estudou analiticamente o tempo médio de primeira passagem em vários tipos de redes, mostrando ser um recurso exploratório bem eficiente. 166 Aplicações práticas desta dinâmica são encontradas nos trabalhos de Travençolo, 167,168 que aplicou este modelo aleatório para detecção de bordas em redes complexas e, baseado nas definições de acessibilidades proposta por Rosvall, 169 estudou as características desta definição utilizando SAW aplicado a ruas de cidades. Mais recentemente, Bertozzi 170 estudou a evolução hierárquica de organizações criminosas e aplicou a caminha auto-excludente como estratégia para capturar os participantes e consequentemente acabar com tais organizações.…”
Section: Passeio Aleatório Auto-excludenteunclassified